Perempuan 65 Tahun dengan Gangguan Skizoafektif Very Late Onset dan Withdrawal Benzodiazepine: Laporan Kasus - Muhammad Rian Fathurrahman; Ricko Eliafiana; Arundhati Nugrahaning Aji; Dyani Pitra Velyani (PT Kalbe Farma Tbk., 2025)
Schizoaffective disorder is characterized by a combination of symptoms of schizophrenia and of affective disorders. This paper reports a 65-year-old female with sychotic symptoms and agitation. The patient was diagnosed as bipolar type schizoaffective with benzodiazepine withdrawal based on the presence of symptoms of schizophrenia and mood involvement and a history of abrupt discontinuation of benzodiazepines. Patient carried out daily activities independently even though her social relations are disrupted. Schizoaffective onset over 60 years is very rare. Unspecific symptoms and comorbidities may delay diagnosis.